2015
DOI: 10.1080/01419870.2015.1015585
|View full text |Cite
|
Sign up to set email alerts
|

Diverse cities and good citizenship: how local governments in the Netherlands recast national integration discourse

Abstract: Western European national policies increasingly portray diversity as negative and migrants as 'others' who do not belong to the national community. This article examines how local governments articulate alternative discourses of belonging based on residents' shared membership in the civic life of the city. In a Dutch case study, the ways in which local policymakers diverge from exclusionary national narratives are examined. It is argued that discourses about urban citizenship offer opportunities for the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…The interviewed policy actors are involved in shaping policies at the (sub)municipal level and sometimes also with organizing their implementation, but they do not deal directly with migrants themselves. A previous study (Hoekstra, 2015) showed the existence of a 'diversity' discourse in Amsterdam and an 'integration' discourse in The Hague. This paper considers where these discourses originate and how they are implemented.…”
Section: Materials and Approachmentioning
confidence: 93%
See 3 more Smart Citations
“…The interviewed policy actors are involved in shaping policies at the (sub)municipal level and sometimes also with organizing their implementation, but they do not deal directly with migrants themselves. A previous study (Hoekstra, 2015) showed the existence of a 'diversity' discourse in Amsterdam and an 'integration' discourse in The Hague. This paper considers where these discourses originate and how they are implemented.…”
Section: Materials and Approachmentioning
confidence: 93%
“…Both cities have a history of formulating policies to govern this diversity. Similar to the national level these have changed significantly over the last decades (Hoekstra, 2015). There are also differences between the cities, notably in their spatial, economic, and political structure, which are based in diverging historical trajectories.…”
Section: Case Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Governmental efforts to regulate the behaviour of their subjects are socially and geographically uneven: they target some groups and places more than others. In particular, residents of migrant background are often expected to demonstrate good citizenship qualities by being self-reliant and taking advantage of opportunities for social mobility (Hoekstra, 2015;Kofman, 2005). In this respect, Schinkel and Van Houdt (2010: 697) talk about the 'twin process' of moralization and responsibilization of citizenship to which residents of migrant background in the Netherlands are subjected, which combines a communitarian focus on their assimilation into the Dutch national culture with an emphasis on individual responsibility and participation.…”
Section: Urban Policy and The Good Citizenmentioning
confidence: 99%